ADVOKASI PERKUMPULAN NARASITA DALAM MEMPERJUANGKAN KETERWAKILAN PEREMPUAN PADA PEMILU LEGISLATIF 2014 - Yanuardi Yanuardi (NATAPRAJA, 2013)
This research aims to understand advocacy of NARASITA organization in striving woman representation in legislative election. This research uses descriptive qualitative research method. Research result shows that advocacy done by NARASITA in legislative election is more focused on efforts to improve quality and quantity of women in Parliament in order to achieve bigger goals in social transformation. Advocacy done is recruitment of potential women to sit on legislative, strengthening capacity, network and campaign. But action done is not yet paying attention on men’s involvement and institutionalizing issues to become political party’s regeneration agenda. Barriers faced by NARASITA in advocating is expensive political fund while potential cadre has limited financial capital, rooted patriarchal culture in political party and society, and too few staff numbers, only 8 people while advocacy area is broad. Kata Kunci : Advocacy, Women Representative, Legislative Election